Can Medicaid be a Solution to the Problem? Underinsurance in Medicaid Expansion Versus Non-Expansion States - Aniyar Izguttinov MPH PhDc; Justin G. Trogdon PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
The positive effects of Medicaid expansions have been extensively documented in the literature. However, it is not clear whether the reform has had an equally meaningful effect with respect to underinsurance, which is the state of having health insurance yet lacking adequate coverage or facing substantial financial risks upon usage of services. Based on a quasi-experimental difference-in-differences approach, we analyzed the data from a nationally representative sample to estimate the effect of Medicaid expansion on the probability of underinsurance among the non-elderly low-income adult population of the U.S. We found no evidence of significant changes in the likelihood of underinsurance due to Medicaid expansion during the first 4 years after the ACA implementation. However, a supplementary analysis of the longer-term impact (2018-2019) suggests that there might be a time lag between Medicaid expansion and its effect on underinsurance. It is important to realize that expansion of coverage alone may not be sufficient to protect millions of Americans, particularly those with low incomes, from underinsurance. It is, therefore, crucial for policymakers to build legislative frameworks that protect individuals from excessive healthcare expenses and prevent treatment avoidance or delay.